Protection Rohingyas through International Adjudication-Decoding Provisional Measures of International Court of Justice in The Gambia vs. Myanmar. - Swargodeep Sarkar (Faculty of Law, Musamus University, 2020)
United Nations Secretary-General Antonio Guterres acknowledged Rohingya, “one of, if not the, most discriminated people in the world”. In Myanmar, a country with a Buddhist majority, around a million Rohingya who is the minority having their language and culture, have been persecuted for decades. In the year 2014 census, Myanmar excluded Rohingya by denying basic citizenship. Thousands of Rohingya have fled to neighbouring States after facing persecution orchestrated by Myanmar security forces with the help of local Buddhist mobs. In this background, the Gambia with the help of Organisation of Islamic Cooperation filed the case in the International Court of Justice, alleging that the actions perpetrated by Myanmar violated the provisions of Genocide Convention 1948 to which both States are the parties. Myanmar rightly questioned the standing of Gambia as the interest of Gambia was not threatened or at stake. So, in the absence of a cause of action or rights of the Gambia not affected even remotely, the International Court of Justice should not entertain the case. One of the major issues before the Court whether the Gambia has stood without being affected directly from the violations alleged to have been committed on the Rohingya. The present author will discuss the provisional measures rendered by the ICJ on 23rd January 2020 and the challenges such as jurisdiction, admissibility, urgency or irreparable prejudice condition, faced by the Court with a special focus on the “Plausibility requirement” in provisional measures.